What do we know about the future of food systems in East and Southern Africa? - Tesfaye Fantaye, Kindie; Hartley, Faaiqa; Thomas, Timothy S.; Gbegbelegbe, Sika; Gabriel, Sherwin (International Food Policy Research Institute, 2025)
Food demand in East and southern Africa (ESA) is expected to be three to nine times higher by 2050 (relative to 2010), depending on the emerging economic and demographic trends.